Design and conduct of early clinical studies of immunotherapy agent combinations: recommendations from the task force on Methodology for the Development of Innovative Cancer Therapies. (10th September 2018) - Smoragiewicz, M; Bogaerts, J; Calvo, E; Marabelle, A; Perrone, A; Seymour, L; Shalabi, A; Siu, L L; Tabernero, J; Giaccone, G; ,
Abstract: The Methodology for the Development of Innovative Cancer Therapies task force considered aspects of the design and conduct of early studies of combinations of immunotherapy agents during their 2018 meeting. The task force defined the relevant data to justify combination clinical trials, which includes a robust hypothesis for the combination, pre-clinical data with evidence of efficacy and an understanding of the pharmacodynamics effects of each agent, and ideally evidence of single agent activity. Evaluation of pharmacodynamic biomarkers is critical in early phase combination trials, and should be incorporated into trial objectives and go/no-go decisions. The task force also identified the need to develop assessment tools and end points that capture the unique patterns of tumour responses to immunotherapy, including pseudoprogression and hyperprogression. At least one additional tumour measurement before baseline and an early CT scan (at 4 weeks for example) would help define the incidence of hyperprogression, although a common definition is needed. Finally, the task force highlighted substantial redundancy and inefficiency in the combination immunotherapy space, and recommended the adoption of innovative trial designs.